First Case of Human Brucella canis Infection in the Netherlands. (2nd June 2022) - Kolwijck, Eva; Lutgens, Suzanne P M; Visser, Vanessa X N; van Apeldoorn, Marjan J; Graham, Heather; Koets, Ad P; Schrauwen, Michelle M W P; Reubsaet, Frans A G; Broens, Els M; Kortbeek, Laetitia M
Abstract: A patient was diagnosed with Brucella canis following exposure to infected dogs in her breeding facility. Transboundary spread of B. canis through (illegal) import of infected dogs to non-endemic countries in Europe suggest that B. canis infection should be considered in European patients with occupational exposure to dogs.